Attack by the mahogany shoot borer, Hypsipyla grandella Zeller (Lepidoptera: Pyralidae), on the Meliaceous trees in the Peruvian Amazon - Yamazaki, Saburo (1992)
The infestation of meliaceous species by the mahogany shoot borer, Hypsipyla grandella ZELLER, was investigated in plantation areas of the Peruvian Amazon. Damage was particularly great on line plantings and plantings in opened areas. Cedrela odorata was attacked by H. grandella from 0 to 10 times during 16 months, averaging 3 attacks per tree. The upper main stem of trees was more frequently attacked than offshoots or middle stems. First to second instar larvae were mostly found in the offshoot, whereas the older larvae were found most frequently in the upper main stem. Both C. odorata and Swietenia macrophylla sprouted 3 to 5.5 times a year, averaging 3.7 and 4.4 times, respectively. Flushing was concentrated in the rainy season and was rare in the middle of the dry season, resulting in a rapid increase of H. grandella in the former. The attack of Hypsipyla on the main stem triggered sprouting, which seemed to keep the pest density at a certain level in the dry season. The percentage of newly attacked trees per month tended to be slightly higher in C. odorata than in S. macrophylla.